Pengaruh Video Interaktif Powtoon Terhadap Hasil Belajar Tematik Tema Daerah Tempat Tinggalku Siswa Kelas IV SD Negeri 65 Palembang - Marcela, Ovi; Akhbar, M. Taheri; Surmilasari, Nora (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study is to find out what happens to students in thematic learning with the theme of the area where I live, especially in the content of science lessons and to determine the effect of Powtoon's interactive video on the thematic learning outcomes of the area where I live, fourth grade students of SD Negeri 65 Palembang. This research method only refers to the Posttest-Only Control Design method. The sampling technique used is Simple Random Sampling. class IV A used Powtoon interactive video & class IV B was used instead of Powtoon interactive video learning. The statistical data collection technique used is experimental. Statistical data analysis technique using ttest. As the experiment was given, until the experimental design in the Posttest data using the t-testwas obtained the value of t _hitung=13.37 and (dk) = n_1+n_2-2=30+13-2=41 and = 0.025 until was found. t_table = 2.019. because 13.37 2.019, then Hₒ is rejected, so Hₐ is accepted. So it can beconcluded that there is an effect of Powtoon's interactive video on the thematic learning outcomes of the area where I live for fourth grade students at the State Elementary School 65 Palembang.